Desymmetrisation of 1,3-diols and their diacetates under enzymatic heterogeneous catalysis and synthesis of 1,3-diols under continuous flow conditions - Pamarthy, Varsha Siri (2019)
Piperidones are present in many biologically important compounds. One of the key steps in the synthesis of one such piperidone, N-benzyl-5- methoxypiperidone, is the desymmetrisation of 1,3-diol, N-Benzyl-5-hydroxy-4- (hydroxymethyl)pentanamide or 1,3-diacetate, N-Benzyl-5-acetoxy-4- (acetoxymethyl)pentanamide, which provide access to the (R)- and (S)- enantiomers of the piperidone, respectively. The main aim of this thesis is to develop a flow process to perform synthesis and desymmetrisation of the 1,3- diol. Lipase AK from Pseudomonas fluorescens was immobilised by cross-linking using glutaraldehyde on (3-aminopropyl)triethoxysilane functionalised Fe3O4 magnetic nanoparticles and silica nanospheres (KCC-1), and by physical adsorption on covalent triazine-piperazine linked polymer (CTPP-1). Desymmetrisation of 1,3-diol in batch conditions using free lipase AK provided the (R)-monoacetate in up to 93% yield and 92% ee while catalysis of the same reaction by immobilised lipase AK provided the monoacetate in up to 98% yield and 93% ee in 9 h respectively. Under batch conditions, hydrolysis of 1,3- diacetate offered the (S)-monoacetate in up to 54% yield and 93% ee, and 57% yield and 93% ee, in 24 h each, when free lipase AK and immobilised lipase AK were used as the catalysts correspondingly. Amongst the investigated immobilised lipase AK, lipase AK immobilised on Fe3O4 magnetic nanoparticles were found to be the most suitable catalysts for the desymmetrisation reactions as they not only provided the monoacetates in relatively high yields but were also easily separable and maintained their activity up to five reaction cycles. x Since flow reactors are not only energy efficient but also offer improved mixing control and high interfacial area for biphasic reactions, a semi-continuous synthesis of 1,3-diol was developed. Desymmetrisation of 1,3-diol in flow provided the (R)-monoacetate in up to 73% yield and 93% ee. The flow reactor for the hydrolysis of 1,3-diacetate gave the (S)-monoacetate product in up to 81% yield and 95% ee, a marked improvement from 57% yield and 93% ee obtained using a batch process.